Big Data in Context: Legal, Social and Technological Insights - Hoeren, Thomas; Kolany-Raiser, Barbara (Springer, 2017)
Privacy; data protection; data mining; predictive analytics.
Keywords: Language arts.; Arts du langage.; Library & information sciences.; Language Arts & Disciplines / Library & Information Science.; Language arts; privacy; data protection; data mining; predictive analytics; Electronic books.